The Influence of Financial Literacy and Financial Management on The Saving Interest of Final Semester Management Students (Case Study at University of Tribhuwana Tunggadewi) - Maria Nining Heldi; Warter Agustim; Willy Tri Hardianto (International Research & Development for Human Beings (IRDH), 2026)
Students, as part of the younger generation, hold a pivotal role in fostering sustainable and responsible financial behavior. Nevertheless, evidence indicates that many continue to display consumptive habits and demonstrate limited interest in saving. This discrepancy highlights a critical gap between financial knowledge and its practical application, underscoring the need for enhanced financial literacy initiatives to bridge the divide and promote healthier financial practices among students. The purpose of this research is to analyze the influence of financial literacy and financial management on the savings interest of final semester management students at Tribhuwana Tunggadewi University, Malang. This study uses a quantitative approach with multiple linear regression analysis method. The data used are primary data obtained through distributing questionnaires to 66 respondents selected using random sampling technique. The results of the study indicate that partially, financial literacy does not significantly influence the interest in saving, as indicated by the calculated t value of 1.235, smaller than the t table of 1.669 and a significance value of 0.221, greater than 0.05. Meanwhile, financial management significantly influences the interest in saving with a calculated t value of 6.267, greater than the t table of 1.669 and a significance level of 0.000, smaller than 0.05. This indicates that financial management is a dominant variable in influencing students' interest in saving. In addition, the results of the study also show that simultaneously financial literacy and financial management influence students' interest in saving.